Free Radical Scavenging Activities of Extracts from Pomelo - Liao, Yongzhi; Qin, Wen; Li, Pengwei; Zhang, Ye; Yi, Xianghui (Asian Journal of Chemistry, 2014)
Under ultrasound, pomelo peel (PP) and pomelo flesh (PF) were extracted with acetone, ethanol, water and ethyl acetate solvents at 70 °C to offer acetone extract (PAE), ethanol extract (PEE), water extract (PWE), ethyl acetate extract (PAEE, acetone extract (FAE), ethanol extract (FEE), water extract (FWE) and ethyl acetate extract (FAEE), respectively. Their free radical scavenging activities were evaluated and compared with the common antioxidant butylated hydroxytoluene, employing DPPH• assay, ABTS+• assay, O2–• assay and OH• assay. The results showed that all the extracts displayed good radical scavenging activities, with IC50 less than standard value 10 mg/mL. It is important to point out that all these eight extracts demonstrated better scavenging activity than the commercial antioxidant BHT in OH• assay. The extract solvents were found to have important effect on their radical scavenging activities.